1999
DOI: 10.1046/j.1365-2788.1999.00217.x
|View full text |Cite
|
Sign up to set email alerts
|

Excess of non‐right handedness among individuals with intellectual disability: experimental evidence and possible explanations

Abstract: Seventy-three subjects with mild and moderate intellectual disability (ID) of an unknown/idiopathic nature, who had no record of specific deficits in motor control, and 73 normal controls, matched for chronological age and sex, underwent evaluation of handedness. The results confirmed the previously reported excess of non-right handedness among subjects with ID, and suggested that this finding might be indicative of a deviant cerebral organization or atypical lateralization of cerebral representation of functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 53 publications
4
24
1
3
Order By: Relevance
“…In addition, the ID children showed a significantly lower test-retest consistency of hand preference than TD children (as measured by number of hand shifts). These results are in line with others studies showing a relatively low handedness consistency in adults presenting idiopathic mental retardation (Grouios et al, 1999), or more generally in mentally retarded adults (Morris & Romski, 1993;Soper et al, 1987;see also Carlier et al, 2006, andGérard-Desplanches et al, 2006, for similar results with individuals with Trisomy 21 and Williams-Beuren syndrome, two genetic disorders associated with cognitive impairment). We found no significant age-related differences in direction, degree, and consistency of laterality between the two ID groups.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the ID children showed a significantly lower test-retest consistency of hand preference than TD children (as measured by number of hand shifts). These results are in line with others studies showing a relatively low handedness consistency in adults presenting idiopathic mental retardation (Grouios et al, 1999), or more generally in mentally retarded adults (Morris & Romski, 1993;Soper et al, 1987;see also Carlier et al, 2006, andGérard-Desplanches et al, 2006, for similar results with individuals with Trisomy 21 and Williams-Beuren syndrome, two genetic disorders associated with cognitive impairment). We found no significant age-related differences in direction, degree, and consistency of laterality between the two ID groups.…”
Section: Discussionsupporting
confidence: 91%
“…Laterality studies indicate that individuals with DS exhibit increased non-right handedness, and inconsistent hand preference compared to healthy adults (Groen, Yasin, Laws, Barry & Bishop, 2008). This finding is in accordance with laterality studies examining handedness in other populations with intellectual disability of different etiology (e.g., Grouios, Sakadami, Poderi & Alevriadou, 1999).…”
Section: Atypical Cerebral Laterality In Individuals With Dssupporting
confidence: 91%
“…Remarkably, both phenotypes were also reported in the Gdi1 mouse model of MR (D'Adamo et al, 2002). Increased prevalence of left or ambiguous handedness has been reported in various neurological and psychiatric disorders, including MR (Morris and Romski, 1993;Grouios et al, 1999;Mohan et al, 2001). Interestingly, positron emission tomography experiments on two patients carrying OPHN1 mutations revealed a reduction in perfusion in certain regions of the right hemisphere (temporal lobe, striatum, and cerebellum) (V. des Portes, personal communication), supporting the hypothesis that in humans, cognitive deficits could be associated with a reduction in brain asymmetry (Toga and Thompson, 2003).…”
Section: Discussionmentioning
confidence: 79%
“…Because previous studies have shown abnormal handedness and brain asymmetry among subjects with moderate to profound MR (Morris and Romski, 1993;Grouios et al, 1999), we assessed paw preference in mice using the Collins paradigm (Collins, 1985(Collins, , 1991. There were as many right-handed as left-handed subjects in the two genotypes (data not shown).…”
Section: Resultsmentioning
confidence: 99%